O ensino da gramática da língua inglesa, no ensino médio, antes e após a implementação da Proposta Curricular do Estado de São Paulo - Souza, Renato José de (2010)
This study aims at describing and interpreting, from the perspective of public High School teachers of English, two phenomena of human experience lived in two distinct moments: the teaching of English grammar before and after the implementation of Proposta Curricular do Estado de São Paulo, in 2008. This study is theoretically based on the constrast among the structuralist, communicative and literacy view on language, as well as on the conceptions of grammar as discussed by Celce-Murcia & Hilles (1988), Odlin (1994), Possenti (1997), Travaglia (2002), and Larsen-Freeman (2003). The methodological orientation is the hermeneutic-phenomenological one, as perceived by van Manen (1990) and Freire (1998, 2007). The research involves four high school teachers of English from distinct public institutions, who provide information through questionnaires sent by e-mail, followed by online interactions that aim at conforming some of the details previously informed. The outcomes of this study evidence that teachers recognize a new approach to grammar in Proposta Curricular, however, their pedagogical practices are still attached to the structuralist approach. The results also reveal that reproduction, and attempts on changing are the themes that constitute the phenomenon teaching English grammar in High School public institutions until 2007. As from 2008 on, the living of the phenomenon on focus is structured on differences and difficulties. Such a perception provides subsidies for new considerations on teaching grammar in public schools, and for the conceiving of teacher education programs that address contents regarding the teaching of grammar